Identification of Plant Growth Promoting Bacteria Within Space Crop Production Systems - Handy, David; Hummerick, Mary E.; Dixit, Anirudha R.; Ruby, Anna Maria; Massa, Gioia; Palmer, Andrew (Frontiers in Astronomy and Space Sciences, 2021)
As we establish colonies beyond earth, resupply missions will become increasingly difficult, logistically speaking, and less frequent. As a result, the on-site production of plants will be mission critical for both food production as well as complementing life support systems. Previous research on space crop production aboard the International Space Station (ISS) has determined that the spaceflight environment, though capable of supporting plant growth, is inherently stressful on plants. The combined stressors of this environment limits yield by stunting growth, as well as increasing susceptibility to infection by plant pathogens such as Fusarium spp. We propose that a consortium of space-viable, plant growth-promoting bacteria (PGPB) could assist in mitigating challenges to plant growth in a sustainable fashion. Here, we utilize biochemical and phenotypic assessments to identify potential PGPB derived from isolates from the VEGGIE crop production system aboard the ISS. These assays confirmed the presence of bacteria capable of producing and/or interfering with plant hormones, facilitating plant uptake of high-value target nutrients for plants such as iron and phosphorus, and able to inhibit the growth of problematic fungal species. We discuss our findings with regards to their potential to support plant growth aboard spaceflight platforms as well as the moon and Mars.